1987
DOI: 10.1073/pnas.84.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of Ly-1, a membrane glycoprotein of mouse T lymphocytes and a subset of B cells: molecular homology to its human counterpart Leu-1/T1 (CD5).

Abstract: We report the isolation of cDNA clones of the mouse lymphocyte differentiation antigen Ly-l. One of these cDNA clones was confirmed to be full-length by DNA sequencing and by expression of Ly-1 by L cells transfected with this clone. Analysis of the predicted amino acid sequence indicated that the Ly-1 polypeptide is synthesized with a 23 amino acid leader and that the mature protein consists of an aminoterminal region of 347 amino acids, a transmembrane sequence of 30 residues, and a carboxyl-terminal region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…It was ruled out as encoding Ly-1 by chromosomal mapping {see below]. Comparison of LYAR to the Ly-1 sequences, subsequently elucidated by others {Huang et al 1987), showed that they encoded polypeptides with no significant similarity.…”
Section: Isolation Of a Edna Encoding A Zinc Finger Protein From A Momentioning
confidence: 99%
“…It was ruled out as encoding Ly-1 by chromosomal mapping {see below]. Comparison of LYAR to the Ly-1 sequences, subsequently elucidated by others {Huang et al 1987), showed that they encoded polypeptides with no significant similarity.…”
Section: Isolation Of a Edna Encoding A Zinc Finger Protein From A Momentioning
confidence: 99%
“…However, the cytoplasmic tail of CD5 is encoded in three exons. The introns in the chicken CD5 gene are localized similarly to the corresponding human and mouse introns [4,12]. However, immediately after the stop codon there is an intron in the human sequence that is not found either in our clone or in the genomic DNA of H.B2 strain chicken.…”
Section: The Organization Of Chicken Cd5 Genementioning
confidence: 68%
“…Chicken CD5 is structurally conserved, especially in its cytoplasmic domain which includes identical regions to mammalian sequence with potential functional motifs [4,5]. In chicken the CD5 is expressed at high levels on all ab T cells, whereas a low or intermediate expression is found on gd T cells depending on their tissue location [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, of key importance for gene cloning and expression studies, these complementary tools provide the ability to select cells expressing particular molecules or variants thereof. Thus, among other things, they allowed us to clone the murine CD8 and CD5 genes (63)(64)(65) and to explore the gene amplification (double-minute/minichromosome) mechanism (66) that controlled the level of expression of the CD8 gene cloned into a nonlymphoid cell line.…”
Section: Somatic Cell Genetics Modern Stylementioning
confidence: 99%